Difficult texts: John 1.18 a – on seeing God - Lindley, Richard (Theology, 2015)
The biblical accounts of seeing (and hearing) God are mixed in kind, but the clear assumption of most traditions is that no one can, in fact, see God. There was consistency in this respect with the results of a recent survey of Winchester churchgoers’ perceptions of God, which also produced one or two surprises. Seeing (and hearing) God is a matter of interpretation, and has much in common with signs and analogies.